2019
DOI: 10.1093/ptep/ptz115
|View full text |Cite
|
Sign up to set email alerts
|

On the gauge-invariant path-integral measure for the overlap Weyl fermions in 16 of SO(10)

Abstract: We consider the lattice formulation of SO(10) chiral gauge theory with left-handed Weyl fermions in the 16-dimensional spinor representation ($\underline{16}$) within the framework of the overlap fermion/Ginsparg–Wilson relation. We define a manifestly gauge-invariant path-integral measure for the left-handed Weyl field using all the components of the Dirac field, but the right-handed part of it is just saturated completely by inserting a suitable product of the SO(10)-invariant ’t Hooft vertices in terms of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 227 publications
0
13
0
Order By: Relevance
“…Even if it condenses, it is not expected to gap out the Weyl fermions if its vaccum expectation value is small (but it will Higgs down the gauge group), so the theory remains gapless in the fermion sector in all phases. However, sufficiently strong Higgs condensation of TrΦ bi (or Φ 1 equivalently) can lead to symmetric mass generation (SMG) [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] as discussed previously.…”
Section: 37)mentioning
confidence: 99%
See 1 more Smart Citation
“…Even if it condenses, it is not expected to gap out the Weyl fermions if its vaccum expectation value is small (but it will Higgs down the gauge group), so the theory remains gapless in the fermion sector in all phases. However, sufficiently strong Higgs condensation of TrΦ bi (or Φ 1 equivalently) can lead to symmetric mass generation (SMG) [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] as discussed previously.…”
Section: 37)mentioning
confidence: 99%
“…The Symmetric Mass Generation (SMG) mechanism is explored in various references, for some selective examples, by Fidkowski-Kitaev[35] in 0+1d, by Wang-Wen[36,37] for gapping chiral fermions in 1+1d, You-He-Xu-Vishwanath[38,39] in 2+1d, and notable examples in 3+1d by Eichten-Preskill[40], Wen[41], You-BenTov-Xu[42,43], BenTov-Zee[44], Kikukawa[45], Catterall et al[46,47], Razamat-Tong[48,49], etc.12 Here fermions are anti-commuting Grassman variables, so this expression ψψψψ is only schematic. The precise expression of ψψψψ includes additional spacetime-internal representation indices and also includes possible additional spacetime derivatives (for point-splitting the fermions to neighbor sites if writing them on a regularized lattice).…”
mentioning
confidence: 99%
“…Based on the Nielsen-Ninomiya fermion doubling of the free fermion theory, the 16 + ⊕ 16 − can be regarded as the realization of the chiral matter 16 + and the mirror matter 16 − (anti-chiral with complex conjugated representation). Based on a generalization of gapping mirror fermion [50] by suitable nonperturbative interactions (see an overview from [51][52][53][54][55]), References [12,[56][57][58] suggested that the mirror matter 16 − can be fully gapped without breaking the Spin(10) group. It is shown in [12] that the gapping 16 − without breaking Spin( 10) is consistent with the classification of all invertible local and global anomalies from the cobordism classification [12,13].…”
Section: Representation Of Internal/gauge Symmetry Groupsmentioning
confidence: 99%
“…The issues of mirror fermion doubling [83] on the mirror world, depending on the precise anomaly matching on the mirror sector, may be fully trivially gapped (if anomaly-free), or may be topologically ordered gapped with TQFT. These issues are tackled in many recent (selective) works [13,[84][85][86][87][88][89][90][91][92][93].…”
Section: Summary Of Ultra Unification In Drawingsmentioning
confidence: 99%